Analisa Figure-Ground kawasan permukiman Islam: Studi kasus Kampung Kauman, Malang - Fitriyah, Fifi Nadlilatul (Maliki Interdisciplinary Journal, 2024)
The history of the development of Islam in Indonesia has left inheritance/results of a very valuable culture. A settlement that acts as one of the cultures of the Islamic Age (Civilization) forms the identity of an area that helped enrich the appearance in the whole city. Kauman Village in Malang City marks the emergence of residential areas in the city center with other residential areas. The whole article can be divided into several main parts that contain a description of the characteristics of settlement patterns with the case study of Kauman Village in Malang, the spatial pattern of settlements as well as the impact of its formation. The study produced components that support the formation of colonies, components that do not support, and components that correct or enrich components that are conceptually designed. In the future, the development of the Kauman Village environment is expected to strengthen Kauman's identity as one of the Muslim settlements in Malang City (pay attention to the supporting components of Islamic creed), without damaging or removing existing historical values and the image of the region as part of a community and inheritance conservation area culture.